The Influence of Learning Style and Motivation On Students' Learning Achievement in Entrepreneurship and Archives Science Courses in the Covid-19 Pandemic at Amik Lamappapoleonro Soppeng - Amriadi Amriadi; Zul Fadly (Jurnal Ilmu Manajemen Profitability, 2023)
In this research process, the researcher applied a quantitative approach to the type of ex post facto (correlational) research. The examination system is carried out at the Amik Lamappapoleonro Soppeng campus. Samples or research participants are students III. Semester Computer Management Amik Lampapoleonro Soppeng Study Program 2019/2020 academic year, totaling 50 students, the variables used in this study were learning styles (X1), achievement motivation (X2) and student performance in semester III of the Study Program Entrepreneurship and Archives course Management. Researchers used data collection techniques to measure a learning style variable and achievement motivation using a Likert Scale questionnaire measuring instrument and the documentation method was used to measure student achievement learning variables. In this study using data, namely descriptive analysis as a tool to measure the Mean, Median, Mode. The product and moment system uses a correlation analysis with a significant level of 5% as a measure for the hypothesis. From the results of testing that is influential. there is a significant and positive relationship (influence) in which student learning styles and student learning in Entrepreneurship and Archives courses with a contribution of 11.4 student learning styles. This means that the student style system in learning is very good will be directly proportional to student learning achievement. There is a significant and positive influence on student achievement motivation with learning achievement in the Informatics Management study program at the Amik Lamappapoleonro Soppeng campus in the Entrepreneurship and Archives course with a contribution of 14.2% to student achievement motivation, namely that if it is very good student achievement motivation so that learning achievement students would be great. In terms of research it has a significant influence between motivation and student achievement learning styles with student achievement learning in the Entrepreneurship and Archives course on the Amik Lamappapoleonro Soppeng campus with a linear regression equation